EDUKASI PENANGANAN PASCAPANEN PRODUK HORTIKULTURA PADA PEDAGANG DI PASAR TRADISIONAL BLAMBANGAN - Yuvita Lira Vesti Arista (Jurnal Abdimas Gorontalo (JAG), 2023)
Postharvest losses in horticultural products reach 45-55%, the main cause of postharvest losses in fruit and vegetables is caused by the product losing water due to respiration and transpiration processes which reduce product weight. Until now, Indonesia still contributes a very large postharvest loss, this is due to the lack of awareness and knowledge from both farmers, traders, and consumers regarding good postharvest handling. Most of the post-harvest losses occur during the marketing process, and this is what makes traders suffer a lot of losses. Therefore, educational activities are needed for post-harvest handling of horticulture products to prevent these losses, especially in the Blambangan Banyuwangi Market. Post-harvest handling that can be carried out by traders to prevent quality degradation of horticultural products includes sorting, trimming, grading, modifying packaging, and modifying storage. Educational activities for post-harvest handling of horticultural products for traders in the Blambangan traditional market run enthusiastically and can be declared successful. All participants can understand the entire material presented, not only that the participants are also able to implement the material directly starting from the process of sorting, trimming, and grading the products they sell. Participants were also able to apply packaging technology starting from selecting the appropriate type of packaging plastic and also making perforated holes in the plastic to reduce the rate of respiration so that fruit and vegetable products sold have a longer shelf life.